Can marine-derived fungus Neosartorya siamensis KUFA 0017 extract and its secondary metabolites enhance antitumor activity of doxorubicin? An in vitro survey unveils interactions against lung cancer cells - Ramos, A.A. (2020)
Doxorubicin (Dox) is one of the most successful anticancer drugs in use. However, chemoresistance is one of the main limitations that patients face. Therefore, development of new strategies to improve the efficacy of Dox is needed. Marine-derived fungi are especially promising sources of new anticancer compounds. In this work, antitumor activity of crude ethyl extract of the cultures of the marine-derived fungus Neosartorya siamensis KUFA 0017 (NS), combined with Dox, was evaluated in six cancer cell lines. To evaluate possible mechanisms involved in the eventual improvement of Dox's cytotoxicity by NS extract, effects on DNA damage, cell death, ultrastructural modifications, and intracellular accumulation of Dox were assessed. The NS extract demonstrated a significant enhancement of Dox's cytotoxic activity in A549 cells, inducing DNA damage, cell death, and intracellular accumulation of Dox. Additionally, the cytotoxic effect of eight compounds, isolated from this extract, that is, 2,4-dihydroxy-3-methylacetophenone-(C1), nortryptoquivaline-(C2), chevalone C-(C3), tryptoquivaline H-(C4), fiscalin A-(C5), epi-fiscalin-C (C6), epi-neofiscalin A-(C7), and epi-fiscalin A-(C8), alone and combined with Dox was also evaluated in lung cancer cells. The cytotoxic effect of Dox was potentiated by all the isolated compounds (except C1) in A549 cells. Therefore, we concluded that NS extract potentiated cytotoxicity by inhibiting cell proliferation, increasing intracellular accumulation of Dox, and inducing cell death (possibly by an autophagic process). The isolated compounds also enhanced the activity of Dox, supporting the potential of this sort of combination. These data call for further studies to characterize drug interactions and underlying mechanisms.